Pengaruh Financial Behaviour dan Financial Attitude terhadap Perkembangan Usaha Mikro Kecil dan Menengah di Kota Jambi - Victor Diwantara; Muhammad Ali Umardhani Panggabean; Sissah Sissah (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study aims to reveal Financial Behavior and Financial Attitude influence the development of micro, small and medium enterprises in Jambi City. This thesis uses a quantitative approach using multiple regression statistical analysis methods partially and simultaneously with a sample of 60 MSMEs. The results of the study indicate that Financial Behavior has a significant influence on the development of MSMEs in Jambi City. Financial attitude has a significant influence on the development of MSMEs in Jambi City. Financial Behavior and Financial Attitude together or simultaneously have a significant influence on the development of MSMEs in Jambi City. In business development, good knowledge is needed to help MSMEs to be innovative and produce new ideas to develop their businesses and knowledge management can help companies to develop a healthy and positive work culture.